THEORY AND PRACTICE OF PICTORIAL AVANT-GARDE IN THE CREATION OF THE UKRAINIAN ARTIST DAVID BURLYUK - KARPOV, VIKTOR (Studiul Artelor şi Culturologie: Istorie, Teorie, Practică)
Modeling the theory of the Ukrainian pictorial avant-garde based on the study of the theoretical views of avant-garde artists is an urgent scientific task of art history. The theory of the avant-garde unites a number of concepts of co-existing artistic currents with its ideals of the human creator and constitutes a certain integral essence of various aesthetic and artistic features. Avant-garde art, as the art of a new and unknown future, needed a theoretical basis for explaining the nature of artistic creation, interpreting it as a synthesis of the conscious and unconscious, the role of the artist and the viewer in their dialectical unity, the importance of the artistic process in social progress. Davyd Burlyuk became a bright follower of the ideas of the avant-garde, which stood out in addition to artistic creativity and its theoretical justification. The Ukrainian avant-garde is built on David Burlyuk’s concept of movement and change. At the center of the artist’s theoretical views is the creative personality with its freedom of choice of individual self-expression. The artist’s views on the essence of avant-garde art became the theoretical basis of the avant-garde in the crowd of traditional ones, which allowed the new art to occupy its own separate place. David Burlyuk’s theoretical canons for the construction of the composition of the work by the method of shifted construction, multiple perspective, texture, color space, free drawing are the basis of the creation of a new pictorial language, new aesthetics and the reconstruction of the artistic space of culture and a contribution to its development. The formation of the worldview basis of the artist’s creativity took place on the basis of the traditions of his own national culture in organic unity with the European trends of renewal of the artistic space, which is a significant contribution to the development of the world avant-garde.